Effects of lowering dried distillers grains with solubles and wheat middlings with or without the addition of choice white grease prior to marketing on finishing pig growth performance, carcass characteristics, carcass fat quality, and intestinal weights - M D Asmus; Michael D Tokach; Steven S Dritz; Robert D Goodband; Terry A Houser; Joel M DeRouchey; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 225 pigs (PIC 327 × 1050, initially 100.1 lb) were used in a 92-d study to determine the effects of withdrawing high-fiber diets 19 d before market on growth performance, carcass characteristics, fat quality, and intestinal weights of finishing pigs. Pigs were allotted to 1 of 7 dietary treatments (5 or 6 pens/treatment). Treatments were arranged in a 2 × 3 factorial plus control with main effects of added choice white grease (CWG; 0 or 3%) during the withdrawal period (d 73 to 92) and fiber levels of low (corn-soybean meal diet), medium (9.5% wheat middlings [midds] and 15% dried distillers grains with solubles [DDGS]), or high (19% midds and 30% DDGS) during the withdrawal period. Pigs were fed high-fiber (19% midds and 30% DDGS) diets from d 0 to 73. Control pigs were fed low-fiber corn-soybean meal diets from d 0 to 92. No CWG × fiber interactions (P>0.13) occurred except for jowl iodine value (IV), which increased (linear, P<0.03) with increasing DDGS and midds only when CWG was added to the diet during the withdrawal period. Adding CWG during the withdrawal period (d 73 to 92) improved (P<0.02) ADG (1.81 vs 1.94 lb/d) and F/G (3.46 vs 3.19), leading to an overall (d 0 to 92) improvement (P<0.02) in F/G. Carcass yield and backfat depth increased (linear, P<0.05) when low-fiber diets were fed from d 73 to 92. Pigs fed high levels of DDGS and midds had increased (P<0.001) jowl IV, with a larger increase when CWG was added. Feeding low levels of DDGS and midds during the withdrawal period decreased (linear, P<0.01) whole intestine weights, mainly due to the reduction (P<0.02) in rinsed stomach and full large-intestine weights. Lowering dietary DDGS and midds during a 19-d withdrawal period increased yield through reduced large intestine weight and content and lowered jowl IV. The addition of CWG improved F/G but did not improve carcass characteristics.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; DDGS; Fiber; Finishing pig; NDF; Wheat middlings; Withdrawal